The Roles of Educational Stakeholders in the Finnish Education System: Insights for Islamic Education in Indonesia - Yuli Nur Diyanto; Eva Latipah (Jurnal Pendidikan Agama Islam)
Purpose – This study aims to identify the role of educational stakeholders in the Finnish education system and analyse the principles that can be used to improve the quality of Islamic education in Indonesia.